Sectoral Conditions for the Ownership and Rental of Corporate Real Estate - Tomski Piotr (Production Engineering Archives, 2022)
The aim of this study is to analyze the relationship between the sector of the conducted business and the approach to the ownership and rental of real estate used for business purposes, particularly considering the short-term aspect and space sharing. The research uses data obtained from 102 randomly selected Polish enterprises to explore the relationship between the sector and (1) the preferred legal title to real estate (2) acceptance of short-term rental of real estate and (3) acceptance of space sharing. The relationships in all three areas were found. The sectors of production, hotels and restaurants, construction, and transport lean towards ownership. Enterprises operating in the sector of services and trade prefer rental. The sectors of production, hotels and restaurants and transport are skeptical about short-term rental. Services and trade and construction are open to such rental. The sectors of production and hotels and restaurants are skeptical about space sharing. Transport, trade, and construction are clearly open to such an opportunity. The research limitations are as follows: the research is limited to Polish randomly selected enterprises only, and the results cannot be generalized. The originality/value of this paper is revealed in the fact that this paper outlines a short-term rental and ownership perception from an entrepreneurial-managerial view. The novelty of the presented results consists in filling the gap by conducting the research considering the specification of rental and its narrowing down to a short period and space sharing in the context of the sector.